Vanity fair : a novel without a hero - Thackeray, William Makepeace, 1811-1863 (Oxford world's classics (Oxford University Press), 1998)
This classic story of two nineteenth-century social climbers is the basis for countless films and TV series, and one of the UK's "Best-Loved Novels." Before the Real Housewives, there were Becky Sharp and Amelia Sedley. Ruthless and cunning, Becky may have been born in a lower class, but now that she's graduated from school, she's ready to climb up to a better life-and do whatever it takes to get there. Her friend Emmy, however, is the opposite. She may have mastered music, dancing, and embroidery like any young woman of her class, but she utterly lacks a backbone. Together these friends navigate the perils of Regency society as they search for love and happiness. Social battles are waged against the backdrop of the Napoleonic Wars, and when the smoke finally clears, there's no telling who will come out victorious. A satirical masterpiece, Vanity Fair was #14 on The Guardian's list of the 100 Best Novels and #122 in the BBC's "Big Read" poll for the UK's best-loved novel. It has inspired numerous adaptations, from early silent films to a 2004 movie by Mira Nair starring Reese Witherspoon as Becky